SDG8 : sustainable economic growth and decent work for all : concise guides to the United Nations Sustainable Development Goals - Venkatesan, Madhavi (Concise guides to the United Nations Sustainable Development Goals., 2019)
A growth-oriented economy challenges the inclusion of sustainability parameters, as the very elements that promote sustainability can appear incongruous with economic growth. SDG8 - Sustainable Economic Growth and Decent Work for All addresses how sustainability can be included within the present economic framework and surfaces the significance of behavioural change in the attainment of sustainability. The book highlights that successful implementation of SDG8 will rely on culturally sensitive economic policy to ensure that developing countries retain the ability to develop economic systems that align to both the SDGs and cultural norms.SDG8 - Sustainable Economic Growth and Decent Work for All defines the concept of economic growth and decent work, and ultimately, provides the reader with the opportunity to develop a critical analytical perspective with respect to the objectives and attainment of SDG8.Concise Guides to the UnitedNations Sustainable Development Goals comprises 17 short books, eachexamining one of the UN Sustainable Development Goals. The series provides anintegrated assessment of the SDGs from economic, legal, social, environmentaland cultural perspectives.